Analisis User Satisfaction Terhadap Sistem Informasi Website PKL Fakultas Informatika Menggunakan Metode EUCS - Dyah Ayu Indri Hapsari; Darmansah Darmansah; Hari Widi Utomo (STMIK Budi Darma, 2022)
Website Information System Praktek Kerja Lapangan (PKL) Faculty of Informatics Telkom Institute of Technology Purwokerto is a website designed for students which has a function for the purposes of data collection in the implementation of PKl. But from the entire menu provided, there are some menus that can not be used optimally so it is questionable how the level of satisfaction from the website. The purpose of this study is to determine the level of user satisfaction and identify what factors are the constraints of users in using the website so as to know what suggestions are appropriate to be developed. This study uses the approach of EUCS (End User Computing Satisfaction) method which has 5 attributes, namely content, accuracy, format, ease of use, and timeliness. The sample measurement conducted in this study using slovin formula with respondents of 86 students who have used the website PKL Faculty of Informatics. Respondents answers were measured using a likert scale with data that first measured the validity test and reliability test using SPSS software. Then the results obtained are the average value of the overall user was satisfied with obtaining an average satisfaction score of 3.5. Attribute content obtain an average value of 3.6 that is satisfied category, attribute accuracy obtain an average value of 4.2 that is very satisfied, attribute format obtain a number 3.4 that is satisfied, attribute ease of use obtain a number 3.4 that is satisfied, attribute timeliness obtain a number 3.4 that is satisfied